Clinicopathology Examining of Pericarditis in Patients who Referred to Afshar Hospital in Yazd Province During the Years 2009-2014 - Shokouh Taghipour Zahir, Ali Talebi, Sajjad Ramezanzade (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Pericarditis is an inflammation of the outer layer of the heart. Pericardial effusion is an abnormal accumulation of fluid in the pericardial space. Studies on this disease are mostly related to developed societies and its epidemiological dimensions are not well known in developing countries such as Iran. Therefore, this study was performed to evaluate the clinical pathology of different types of pericarditis referred to Afshar Heart Hospital during the years 2009 to 2014. Method: In this study, 116 patients were examined using a prepared checklist wich includes age, sex, year of hospitalization, clinical symptoms Clinical examinations, echocardiographic evidence, pathological findings (types of pericarditis) and finally recovery and death. The collected data were entered into SPSS software and analyzed using Chi-Square test, and P-values0.05 were considered statistically significant. Results: This study was performed on 116 patients with a mean age of 45.123.95, of whom 61 were male (52.6%) and 55 were female (47.4%). The most common type of pericarditis was idiopathic (51.7%). In cancerous pericarditis (81%) and myxedema (33.3%), most patients were female. The most common complaint was 51.7% of patients with dyspnea. The most cardiac auscultation was reduction of heart sounds (56%). Friction rub was heard in auscultation in only 5 patients (3.4%). The most finding in patients’ ECG was normal sinus rhythm with or without tachycardia (62.1%) and typical ECG changes were seen in 15.5% of patients. The most common pathology observed in 43 patients (37.1%) was acute inflammation. As a result, 112 patients (96.6%) recovered and 4 patients (3.4%) died. Conclusion: As in developing countries, idiopathic type was the most common type of acute pericarditis with the difference that its frequency was lower compared to developed countries. Most young patients with idiopathic pericarditis had a history of a recent cold.